Factors Influencing Students' Intention to use Online Tutoring Applications in Jakarta - RA Dyah Wahyu Sukmaningsih; Adam Kurniawan; Ronald Ronald (LPPM Universitas Islam 45 Bekasi, 2023)
As the COVID-19 pandemic has disrupted traditional learning methods, many students have turned to online tutoring as a supplementary source of education. This study aims to identify the factors that influence students' intention to use online tutoring applications. Data was collected from 401 student respondents in Jakarta through a questionnaire, and analyzed using smart PLS. The results show that perceived brand orientation, interactive course features, course quality, perceived usefulness, perceived ease of use, and trust all have a significant impact on students' intention to use online tutoring applications. These findings have implications for the design and promotion of online tutoring applications, as well as for policymakers and educators seeking to support student learning in the era of COVID-19.